PENINGKATAN LITERASI SAINS MELALUI PEMANFAATAN LABORATORIUM IPA DI SMP - Agastya, Widha Nur (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2017)
This study is a qualitative research library research with triangulation source documents used as a reference for the discussion. The discussion in this is to increase science literacy through the use of science laboratories in secondary school. As has been done PISA study in 2015 that Indonesia in the field of science was ranked 9th from the bottom. Reviews of this study are expected to contribute to the solution of science that can be used as a reference resource for future researchers. The position of the science laboratory in the SMP can be used as a tool to improve science literacy in Indonesia. Increased utilization of laboratory science in junior high, in terms of governance are as follows: 1) the availability of laboratory, 2) the availability of SOP (Standard Operating Procedure), 3) the availability of the order of minimum security for laboratory users. For a school that is not in the lab, the teacher can take advantage of secondhand goods which can be used for simple laboratory, besides that teachers can use virtual laboratories practice in the learning process. Keywords: Science Laboratory, Virtual Laboratory, Science Literacy.